(untitled) - Schlichter, Detlev S. (New Jersey, 2014)
Paper Money Collapse: The Folly of Elastic Money, Second Edition challenges the mainstream consensus on money and monetary policy.
Keywords: Paper money,Money supply,Credit,Tiền giấy,Cung ứng tiền tệ,Thẻ tín dụng